2014
DOI: 10.1016/j.bmcl.2014.07.062
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-ethyltryptamines as dual dopamine–serotonin releasers

Abstract: The dopamine (DA), serotonin (5-HT), and norepinephrine (NE) transporter releasing activity and serotonin-2A (5-HT2A) receptor agonist activity of a series of substituted tryptamines are reported. Three compounds, 7b, (+)-7d and 7f, were found to be potent dual DA/5-HT releasers and were >10-fold less potent as NE releasers. Additionally, these compounds had different activity profiles at the 5-HT2A receptor. The unique combination of dual DA/5-HT releasing activity and 5-HT2A receptor activity suggests that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 36 publications
2
37
0
1
Order By: Relevance
“…Again in a collaborative effort with Dr. Rothman (NIDA), it was found that α-ET isomers behaved differently as releasing agents at SERT, DAT, and NET; EC 50 values for S (+)α-ET and R (-)α-ET were 20 and 68 nM, at SERT, and 64 and 900 nM at DAT, respectively, and >10,000 at NET. 18 Blough et al, 114 at nearly the same time, published similar findings: EC 50 values for S (+)α-ET and R (-)α-ET were 35 and 55 nM at SERT, and 55 and 654 nM at DAT, but showed higher potency at NET (592 and 3,670 nM, respectively) even though still reduced compared to potency at SERT and DAT. S (+)α-ET was also demonstrated to act as a weak 5-HT 2A receptor partial agonist in a calcium mobilization assay whereas R (-)α-ET was inactive.…”
Section: α-Etmentioning
confidence: 73%
See 1 more Smart Citation
“…Again in a collaborative effort with Dr. Rothman (NIDA), it was found that α-ET isomers behaved differently as releasing agents at SERT, DAT, and NET; EC 50 values for S (+)α-ET and R (-)α-ET were 20 and 68 nM, at SERT, and 64 and 900 nM at DAT, respectively, and >10,000 at NET. 18 Blough et al, 114 at nearly the same time, published similar findings: EC 50 values for S (+)α-ET and R (-)α-ET were 35 and 55 nM at SERT, and 55 and 654 nM at DAT, but showed higher potency at NET (592 and 3,670 nM, respectively) even though still reduced compared to potency at SERT and DAT. S (+)α-ET was also demonstrated to act as a weak 5-HT 2A receptor partial agonist in a calcium mobilization assay whereas R (-)α-ET was inactive.…”
Section: α-Etmentioning
confidence: 73%
“…S (+)α-ET was also demonstrated to act as a weak 5-HT 2A receptor partial agonist in a calcium mobilization assay whereas R (-)α-ET was inactive. 114 …”
Section: α-Etmentioning
confidence: 99%
“…23 While most of the vinylogous analogs follow the DA/NE release trend, a few compounds show selectivity for DAT or NET. Recently, we identified a group of tryptamines that are >10-fold selective for releasing DA relative to NE.…”
Section: Resultsmentioning
confidence: 99%
“…Tryptamine acts as a non‐selective serotonin receptor agonist and can trigger the release of serotonin, norepinephrine, and dopamine. Tryptamine preferentially evokes serotonin and dopamine release over norepinephrine release . Increased peripheral serotonin was associated with obesity, which could inhibit energy expenditure by blunting the thermogenic program induced by activation of β‐adrenergic receptors in brown and beige adipocytes .…”
Section: Discussionmentioning
confidence: 99%